A study on the factors influencing service quality dimensions towards organizational performance at ProEight Offshore Engineering Sdn. Bhd. / Muhammad Hafiz Md Radzi - Md Radzi, Muhammad Hafiz (Faculty of Business and Management, Universiti Teknologi MARA, 2011)
This thesis presents a study, which has sought to take steps towards increasing knowledge on the performance of the service quality provided by ProEight Offshore Engineering Sdn. Bhd. ProEight Offshore Engineering is one company that focus on delivering refurbishment service to the related industry and at the same time, the company also do a minor production. It is noteworthy to investigate the performance of service quality provided by ProEight Offshore Engineering Sdn. Bhd. in order for ProEight to take up competitive position against international companies upon their ability to deliver quality services to the customers throughout Malaysia. The research title “A Study on the Factors Influencing Service Quality Dimensions towards the Organizational Performance at ProEight Offshore Engineering Sdn. Bhd.” had been conducted by using Zeithaml et’s (1996) theoretical framework to measure the organizational performance at ProEight Offshore Engineering Sdn. Bhd. This research has been answered by all 34 respondents through questionnaire. The Statistical Package for the Social Science (SPSS) version 14.0 has been used to summarize the data. As a conclusion, the result indicates ProEight customer have a high customer satisfaction towards assurance and empathy dimensions in service quality provided by ProEight Offshore Engineering Sdn. Bhd. and assurance is the elements of service quality that contributed most in service quality performance. Lastly, the recommendations are made based on several logical factors and impact of current situation to the service quality practiced.